Meningkatkan Kosakata Bahasa Arab Anak Usia 5-6 Tahun melalui Metode Bernyanyi: Improving Arabic Vocabulary for 5-6 Year Old Children through Singing Method - Ayunita, Siska; Lubis, Hilda Zahra; Hakim, Nurhaliza; Sa’adah Br BB, Nurul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Language skills, especially the ability to master Arabic vocabulary, are very important skills to master, especially in early childhood. Language learning for early childhood is expected to be taught through more interesting activities, one of which is singing. The purpose of this study was to explore improving the Arabic vocabulary of children aged 5-6 years through the singing method. This research method is qualitative research with a literature review derived from the analysis of research journal articles. The results of the study indicate that improving children's vocabulary can be applied by teachers through the singing method well and effectively because teachers have talent, ability and innovation in implementing different learning methods according to the character of students and their schools.